Peripheral Nerve Blocks and Potentially Attributable Adverse Events in Older People with Hip Fracture: A Retrospective Population-based Cohort Study. (September 2021) - Melton, Natalie; Talarico, Robert; Abdallah, Faraj; Beaulé, Paul E.; Boet, Sylvain; Forster, Alan J.; Fernando, Shannon M.; Huang, Allen; McCartney, Colin J. L.; Meulenkamp, Bradley; Perry, Jeff; Power, Barbara; et al.
Abstract : Background: Peripheral nerve blocks are being used with increasing frequency for management of hip fracture–related pain. Despite converging evidence that nerve blocks may be beneficial, safety data are lacking. This study hypothesized that peripheral nerve block receipt would not be associated with adverse events potentially attributable to nerve blocks, as well as overall patient safety incidents while in hospital. Methods: This was a preregistered, retrospective population-based cohort study using linked administrative data. This study identified all hip fracture admissions in people 50 yr of age or older and identified all nerve blocks (although we were unable to ascertain the specific anatomic location or type of block), potentially attributable adverse events (composite of seizures, fall-related injuries, cardiac arrest, nerve injury), and any patient safety events using validated codes. The study also estimated the unadjusted and adjusted association of nerve blocks with adverse events; adjusted absolute risk differences were also calculated. Results: In total, 91, 563 hip fracture patients from 2009 to 2017 were identified; 15, 631 (17.1%) received a nerve block, and 5, 321 (5.8%; 95% CI, 5.7 to 6.0%) patients experienced a potentially nerve block–attributable adverse event: 866 (5.5%) in patients with a block and 4, 455 (5.9%) without a block. Before and after adjustment, nerve blocks were not associated with potentially attributable adverse events (adjusted odds ratio, 1.05; 95% CI, 0.97 to 1.15; and adjusted risk difference, 0.3%, 95% CI, –0.1 to 0.8). Conclusions: The data suggest that nerve blocks in hip fracture patients are not associated with higher rates of potentially nerve block–attributable adverse events, although these findings may be influenced by limitations in routinely collected administrative data. Abstract : Among 91, 563 surgical and nonsurgical hip fracture patients in Ontario between 2009 and 2017, 17.1% (15, 631) received a peripheral nerve block. Administrative data demonstrate that 5.8% (5, 321 of 91, 563) of hip fracture patients experienced a nerve block–attributable adverse event (seizures, fall-related injuries, cardiac arrest, or nerve injury). Receipt of a nerve block was not associated with a higher rate of these adverse events (5.5% among patients receiving a block vs. 5.9% of patients without a block).Supplemental Digital Content is available in the text.